A CLINICAL PROSPECTIVE STUDY OF CHRONIC PANCREATITIS - G, Purushotham; P, Himabindhu; P, Gowthami; M, Jahnavi (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Chronic pancreatitis (CP) is a relentlessly progressive fibroinflammatory process, resulting in the destruction of endocrine and exocrine elements, which may eventually lead to pancreatic insufficiency. Although previous reports on the treatment of CP have yielded considerable data, our study hopes to give validation on managing CP patients conservatively with confidence. Methods: This study was conducted in the Department of General Surgery, SVRRGGH, affiliated with Sri Venkateswara Medical College Tirupati. The materials for the study were collected from patients presenting to the surgery outpatient department and emergency room with the features of CP during the period of March 2020–April 2021 were included in the study. Results: The incidence is high in patients of age group 44.46±9.16, of which 63.3% were males and 36.7% were females. The most common presenting symptom was pain abdomen. All the data were statistically analyzed using software, namely SPSS 21.0 and Instat. Microsoft Word and Excel have been used to generate tables and graphs. Results on continuous measurements are presented on Mean±SD, and results on categorical measurements are presented in number (%). Conclusion: Conservative management shows 100% pain relief, 33.3% had steatorrhea, while surgical management shows 80% pain relief and 80% steatorrhea. Hence patients with CP can be treated effectively with conservative management.